Review: Axial Motion of Material in Rotary Kilns - Elmira Fedorova; Vladimir Morgunov; Kirill Lobko; Elena Pupysheva (Eng, 2025)
The article examines the parameters of axial motion of bulk material in rotary kilns, including bed height, axial velocity, and mean residence time. The review includes summary tables of experiments from the scientific literature, detailing the conditions and ranges of operating parameter variations. Mathematical models from the literature are presented for each of the parameters discussed. The materials of the article cover studies from 1927 to 2025, including analysis of numerous works that were not published in international sources. Based on the review, the necessity of studying the impact of coating formation on the axial motion parameters is highlighted, along with the need for experiments on real facilities and pilot plants.